THERMODYNAMIC STUDIES OF PYRRHOTITE-PYRITE EQUILIBRIA IN THE AG-FE-S SYSTEM BY SOLID-STATE GALVANIC CELL TECHNIQUE AT 518-723 K AND TOTAL PRESSURE OF 1 ATM - Osadchii E.G.; Chareev D.A. (My University, 2006)
The reaction FeS2(cr) + 2Ag(cr) = 'FeS'(cr) + Ag2S(cr) was studied by measuring the temperature dependence of the electromotive force (EMF) of the all-solid-state galvanic cell with common gas space:(-) Pt | Ag | AgI | Ag2 S, ' FeS ', FeS2 | Pt (+)The measurements were carried out in the flow of argon at atmospheric pressure to prevent oxidation. AgI was used as a solid electrolyte. From the measurements of EMF as a function of temperature, two linear (ΔrCp = 0) trends were obtained, which characterize the equilibrium hexagonal pyrrhotite + pyrite (po + py) and the β-γ first-order phase transition in hexagonal pyrrhotite (ΔtrsHm(γ-β) = (4020 ± 200) J mol-1) at (601 ± 2) K. The latter is presumably related to the γ-paramagnetic-β-antiferromagnetic Neel's transition. For these measurements, the lower temperature limit (518 K) corresponds to the equilibrium sulfides + metallic silver (E = 0); and the upper temperature limit (723 K) is determined by the upper temperature at which the contribution of electron conductivity to AgI ion conductive properties may be significant. From experimental results of this study and literature data for Ag2S, the temperature dependence of the gaseous sulfur activity was determined in the following equilibria: pyrite + high-temperature hexagonal pyrrhotite (γ + py), pyrite + low-temperature pyrrhotite (β + py):log a S2 (γ + py) = (15.64 ± 0.035) - (15455 ± 23) · T- 1, (601 < T, K < 723)log a S2 (β + py) = (14.95 ± 0.05) - (15040 ± 28) · T- 1, (518 < T, K < 601)The temperature dependence of the FeS activity in hexagonal pyrrhotite (aFeSpo) calculated for the pyrrhotite-pyrite equilibriumaFeSpo (γ) = (0.528 ± 9.23 × 10- 3) + (2.489 × 10- 7 ± 1.485 × 10- 5) · T, (601 < T, K < 723)indicates that the value aFeSpo = (0.528 ± 0.005) remains almost constant in the mentioned temperature range. At temperatures below 601 ± 2 K, aFeSpo (β) and the Fe/S ratio in β-po decreases with decreasing temperature, which also correlates with the appearance of magnetic order. The compositional extremum (on a T-x diagram) where hexagonal pyrrhotite is in equilibrium with pyrite results in a significant and obvious geological consequence. In all the mineral assemblages that contain hexagonal pyrrhotite and pyrite and that have reached equilibrium at a temperature below (601 ± 2) K, the same pyrrhotite composition will correspond to two different temperatures. However, the minimal temperature principle is acceptable for natural parageneses; and in many cases, the pyrrhotite geothermometer can still be very useful. © 2006 Elsevier Inc. All rights reserved.